Use of Lidocaine Analgesia Prior To Steroid Injection in Reducing Post-Traumatic Hypertrophic Scars - Jameeat Mal, Muhammad Ali Adnan, Majid Hussain, Asadullah Awan, Masroor Ahmad Baloch, Muhammad Khurram Zia, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Hypertrophic scars are painful and can develop after surgery or trauma, with symptoms varying from an intractable allodynia to minor itch. Extraneural and intraneutral structures could be involved in painful scars issue. The standard treatment for hypertrophic scars is intralesional steroid injections. The present study aimed to investigate the lidocaine analgesia for pain relief in post-traumatic hypertrophic scars. Place and Duration: Burn Centre Dr Ruth K.M. Pfao Civil Hospital, Karachi and the department of Plastics and Burn Surgery, Bolan Medical Complex Hospital, Quetta during the period from October 2020 to September 2021. Methodology: Thirty-five patients with post-traumatic hypertrophic scars were enrolled in this study. Steroids were injected through scars with or without Lidocaine (-10°C) applications for 15 seconds. Ethical approval was taken from the institutional ethical committee. In this experimental protocol, two arms were used. In the first arm, two scars on the same patient's body were randomly assigned as control or experimental scars. Patients were used as their own controls because everyone experiences pain differently. Scars were injected into patients once a month, and pain intensity scores were recorded after each injection. A visual analog score (VAS) was used for the evaluation of pain severity or degree in each individual. Results: Of the total 35 hypertrophic scars patients, about 23 (65.7%) and 12 (34.3%) were females and male respectively. The overall mean age was 32.67±5.83 years. All the hypertrophic scars patients with age ranges from 20 to 65 years were enrolled. Of the total lesions, the presence of hypertrophic scars on the arms, shoulder, back, and chest were 7 (20%), 3 (8.6%), 9 (25.7%), and 16 (45.7%) respectively. The visual analogue score for control and pretreated was 2.8±1.42 and 7.91±1.29 respectively. The VAS pain score was significantly associated (p<0.1) with difference in VAS score of control and pretreated scars. Conclusion: The present study found that lidocaine analgesia provides significant pain relief in post-traumatic hypertrophic scars prior to steroid injection. It also provides a safe and effective way for enhancing the management of disease and patient compliance.